(untitled) (TRAKIA JOURNAL OF SCIENCES, 2024)
A study was carried out on the economic efficiency of three herds of the Awassi breed for the period 2021-2023. The animals included in the study amounted to 986 animals in 2021, and 996 animals in 2023. The results of the survey show that during the survey period, herd renovations were carried out at the rate of 32.4%. By the same percentage, the number of rams was reduced, which significantly exceeded those required for the herds and made production more expensive. All natural indicators have been improved. Milk produced for the study period increased by 28.22%, but the established milk yield of 126 liters was below the requirements of the breeding program of 160 liters per milking period. The fertility of the breed increased and reached values of 144% with the requirements set in the breeding program at 110%. The live mass of lambs for sale increased by 4%, but the purchase price increased by 37.49% per 1 kg. On average, farm income increased by 33.35% and expenditure by 27.62%. The increase in costs was due to the higher prices of fodder, which, with the exception of alfalfa hay in the village of Tankovo, was purchased from other farms. In 2021, minimal profit was realized, and in 2023, there was satisfactory profitability, but with a low value of income and expenses. The results of the study prove that farmers experience a dire need of land for the production of animal feed.